Desconstruir a corrupção: o papel do Legislador, príncipe e soberano. A análise do caso no pensamento de Jean-Jacques Rousseau - Eurípedes Martins, Adriano Medeiros (Revista Ágora Filosófica, 2016)
There is no state without subjects. For Rousseau state-building requires the direct participation of citizens. The active participation of citizens will result in the expression of the general will. It is the general will that via social pact, give life and unity to the state. The state is a political body design. The active participation of citizens in order to prevent corruption and dissolution of the company refers to the conception of popular sovereignty. In this mode of sovereignty, citizens would be able to build and maintain the foundations of civil society. Rousseau, as a contractualist, thinks his time and political solutions to the real problems of his time. So it is this scenario between theory and practice, which Rousseau will start to set up the distinction and the relationship of this important tripod: Sovereign, Legislator and Prince.